The Social Reality and Education of Children With Visual Disabilities in The Novel Anak-Anak Cahaya by Ramaditya Adikara - Adene Taqya, Hilya Ayu; Alfian Setya Nugraha (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the phenomenon of social reality and education of children with visual disabilities in the novel